Editorial: New perspectives on gender based violence: from research to intervention, volume II - Rollè, Luca; Ramon, Shulamit (Frontiers in Psychology, 2024)
The European Institute for Gender Equality and the WHO underlined that Gender based violence (GBV) and Violence Against Women (VAW) involve principally women but also men, families and the societies in which they live REF. The GBV and the VAW reinforce the gender inequalities which are steeped in the cultural aspects and gender roles that either support and justify. In 2015 the EU Agency for Fundamental Rights affirmed that violence against women can be considered as a violation of human rights and dignity REF. In the European Union 1 in 3 women experience physical and/or sexual violence, while 1 in 2 experience sexual harassment, 1 in 20 has been raped, and 1 in 5 has experienced stalking. 95% of victims trafficked for sexual exploitation in EU are women. GBV and VAW can manifest indifferent ways, from the most common forms (i.e. Intimate Partner Violence), to the newer forms mediated, for example, by the use of new technology (i.e. the use of devices and online mode). However, Donestic Violence (DV) remains largely under-reported due to fear of reprisal by the perpetrator, hope that DV will stop, shame, loss of social prestige due to negative media coverage: 90% of cases of DV continue to be identified as a non-denounced violence. Violence towards men should also not be neglected, as it increases in number every year. Its dynamics may differ, and most of it is generated by other men in same sex couple.